Shariah inspection of surplus distribution in takaful operations - Soualhi, Younes (KENMS-IIUM Press, 2010)
This research intends to shed light on a number of issues related to surplus distribution in takāful. The first part is devoted to revisiting the main financial concepts related to the surplus such as the underwriting surplus and profit. Modes of distribution such as pro-rata and offsetting will also be discussed in the light of equity principle advocated by SharÊcah. The second part deals with the major juristic views and doctrines delineated in favor of surplus distribution. Legal doctrines such as the ownership or otherwise of the surplus after donation would be meticulously discussed and reviewed in the light of current practices of takāful operators. The last part deals with a general outline of SharÊcah parameters in relation to equitable surplus distribution. This is followed by a scrutiny of surplus distribution practices of some modern takāful operators both in Malaysia and abroad. The research argues that while it is strongly recommended to redistribute the surplus to the participants only, there is a considerable SharÊcah ground allowing takāful operators to share in the surplus for reasons outlined in this research.